Stabilising role of seed banks and the maintenance of bacterial diversity. (28th July 2021) - Wisnoski, Nathan I.; Lennon, Jay T.
Abstract: Coexisting species often exhibit negative frequency dependence due to mechanisms that promote population growth and persistence when rare. These stabilising mechanisms can maintain diversity through interspecific niche differences, but also through life‐history strategies like dormancy that buffer populations in fluctuating environments. However, there are few tests demonstrating how seed banks contribute to long‐term community dynamics and the maintenance of diversity. Using a multi‐year, high‐frequency time series of bacterial community data from a north temperate lake, we documented patterns consistent with stabilising coexistence. Bacterial taxa exhibited differential responses to seasonal environmental conditions, while seed bank dynamics helped maintain diversity over less‐favourable winter periods. Strong negative frequency dependence in rare, but metabolically active, taxa suggested a role for biotic interactions in promoting coexistence. Together, our results provide field‐based evidence that niche differences and seed banks contribute to recurring community dynamics and the long‐term maintenance of diversity in nature. Abstract : Using a multi‐year, high‐frequency time series data from a north temperate lake, we documented stabilising mechanisms of biodiversity, including 1. bacterial taxa exhibited differential responses to seasonal environmental conditions, 2. strong negative frequency dependence in rare, but metabolically active, taxa and 3. preservation of taxa over winter due to seed bank dynamics. Our results provide field‐based evidence that niche differences and seed banks contribute to recurring community dynamics and the long‐term maintenance of diversity in nature.